An IoT approach to positioning of a robotic vehicle - Dvořák, Miroslav; Doležel, Petr (Springer International Publishing AG, 2018)
This paper presents and evaluates one approach to the problems of automatic control of a vehicle movement in a large outdoor area. The positioning of the vehicle in the area is provided by iBeacons, located at the edges of the given surface. The iBeacon is a small and low-power device which periodically transmits its UUID (Universally Unique Identifier) number through the interface of a Bluetooth 4.x. The vehicle should be able to calculate its position according to the power of the signal, considering the location of the iBeacons. To be more specific, the triangulation method is applied to determine the position. According to the set of experiments presented at the end of the paper, the position error of a robotic vehicle is mostly less then 1m.
Lokalizace robotického vozidla pomocí přístupu internetu věcí
Keywords: iBeacon; Trilateration; LLS; RSSI; Bluetooth; Kalman Estimator; iBeacon; trilaterace; metoda nejmenších čtverců; bluetooth; Kalmanův estimátor